Konseling Traumatik: Sebuah Pendekatan dalam Mereduksi Trauma Psikologis - Ummul. L, Misya'lul Millah; Nihayah, Ulin; Nafisa, Amaliya; Qori'ah, Ina (Sultan Idris Journal of Psychology and Education, 2022)
Trauma is an individual's behavior that is not normal because it has experienced an event that is very memorable so that it is psychologically disturbing and difficult to forget. The trauma experienced is very influential on mental health that can result in disrupted activities. When someone has experienced trauma, it is necessary to be handled by experts such as providing psychological counseling which is expected to help his mental health and recover. So, individuals who have experienced trauma really need treatment such as psychological counseling which is expected to make their psychic healthy again. Psychological injuries are just as important as physical injuries, which if they don't get proper treatment, will have a bad impact on the sufferer because the wound gets bigger. The findings in this study that traumatic counseling is a process of giving meaning to clients who have experienced trauma and also giving meaning to counselors who help overcome their clients' trauma and psychological trauma caused by internal and external factors. trauma counseling. In this study using a library research, namely conducting a literature review containing reviews, summaries, and the author's thoughts on several library sources (can be articles, books, slides, information from the internet, etc. In the implementation of the traumatic counseling approach in reducing psychological trauma using several strategies in two stages, namely the stage of traumatic counseling approach, and therapy using counseling techniques.